2016
DOI: 10.1097/prs.0000000000002480
|View full text |Cite
|
Sign up to set email alerts
|

Current Uses of Botulinum Neurotoxins in Plastic Surgery

Abstract: Botulinum neurotoxin is a naturally synthesized microbial protein that has been applied in the management of various disorders. In particular, its application within the realm of plastic surgery is addressed in this article. After evaluating the medical literature, the seven indications with the highest quality trials for the use of botulinum neurotoxin in plastic surgery were as follows: rhytides, facial dystonias, facial nerve palsy and aberrant regeneration, hand tremor, palmar hyperhidrosis, neuropathic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…Recently, many off‐label cosmetic uses of BTA have been introduced . Intradermal injection of BTA was the other technique that has been used off‐label by many clinicians for the purpose of face‐lifting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many off‐label cosmetic uses of BTA have been introduced . Intradermal injection of BTA was the other technique that has been used off‐label by many clinicians for the purpose of face‐lifting effect.…”
Section: Discussionmentioning
confidence: 99%
“…14 It also provides the ability to control sweat and sebaceous glands, providing a smoother skin. 5,17 Studies have confirmed Botox as modality to treat palmar hyperhidrosis.…”
Section: Neurotoxinsmentioning
confidence: 97%
“…4,5 The 3 types are generally constituted in 0.9% sterile, saline (preserved and nonpreserved can be used) with the reconstituted product safely stored for 1 week. The patient’s presentation and treatment areas influence the amount of the product injected.…”
Section: Neurotoxinsmentioning
confidence: 99%
See 2 more Smart Citations